PENGARUH INFLUENCER, BRAND IMAGE, WORD OF MOUTH, DAN PELUANG KARIER TERHADAP KEPUTUSAN PEMILIHAN PERGURUAN TINGGI SWASTA DI KOTA BANDUNG MENGGUNAKAN METODE PLS-SEM - Arijanto, Sugih; Darmawan, Nazwa Aulia; Bakar, Abu; Mukti, Yoanita Yuniati (Teknik Industri Unikom, 2024)
The competition among private universities (PTS) in Bandung is intensifying as Generation Z, which dominates the student population, becomes increasingly reliant on social media. This study aims to identify and analyze the key factors influencing PTS selection to provide insights for improving marketing strategies. A quantitative approach was used with purposive sampling, involving 136 respondents, and data was analyzed using the PLS-SEM method. The results indicate that among the four tested variables, career opportunities and word of mouth significantly influence student’s decisions in choosing a PTS, whereas influencers and brand image do not have a significant impact. To enhance career appeal, PTS should maintain a strong balance between theory and practice in study programs. Additionally, improving student satisfaction and involving parents can strengthen the effectiveness of word-of-mouth promotion. These findings offer valuable input for PTS in refining their marketing approaches to attract more students in an increasingly competitive education sector.